Sudden Unexplained Nocturnal Death Syndrome in Central China (Hubei): A 16-Year Retrospective Study of Autopsy Cases. Issue 9 (March 2016) - Chen, Zhenglian; Mu, Jiao; Chen, Xinshan; Dong, Hongmei
Abstract : Abstract: A retrospective study was conducted at Tongji Forensic Medical Center in Hubei (TFMCH) from 1999 to 2014. Forty-nine cases of sudden unexplained nocturnal death syndrome (SUNDS) were collected. The SUNDS rate was 1.0% in the total number of cases, in which an incidence was fluctuating over the years. Interestingly, April and January, and 3:00 to 6:00 AM were the peak months and times of death. Among the decedents, farmers and migrant workers accounted for 67.3%. The syndrome predominantly attacked males in their 30s. One victim had sinus tachycardia. Thirteen victims (26.5%) were witnessed and had abnormal symptoms near death. Macroscopically, compared to sudden noncardiac deaths, the weights of brain, heart, and lungs had no statistical difference in SUNDS. Microscopically, the incidence of lung edema (45 cases, 91.8%) was significantly higher in SUNDS group than in the control group (27 cases, 55.1%). 82.9% of 35 SUNDS cases examined displayed minor histological anomalies of the cardiac conduction system (CCS), including mild or moderate fatty, fibrous or fibrofatty tissue replacement, insignificant stenosis of node artery, and punctate hemorrhage in the node area. These findings suggested that minor CCS abnormalities might be the substrates for some SUNDS deaths. Therefore, SUNDS victims might suffer ventricular fibrillation and acute cardiopulmonary failure before death. Further in-depth studies are needed to unveil the underlying mechanisms of SUNDS.